The influence of EPD data on LCA results. Issue 1 (1st September 2022) - Tozan, B; Stapel, E; Sørensen, C; Birgisdóttir, H
Abstract: The built environment is responsible for reaching global climate targets such as the Paris agreement and carbon neutrality in 2050. It is a well-known fact that buildings stand for 37% of global greenhouse gas (GHG) emissions, where 10% is due to emissions from the production of building materials, while the remaining 27% comes from energy consumption [1]. The awareness of the major contribution to global GHG emissions from the built environment has enabled a great interest in developing more sustainable buildings, reducing the contribution to GHG emissions, and conducting life cycle assessments (LCA) of buildings in Denmark. In March 2021 a national strategy towards more sustainable buildings was introduced, which requires an LCA of new buildings, and compliance with the limit value of 12 kg CO2 e/m 2 /year for new buildings with > 1000 m 2 . The strategy underlines the urgency of educating the Danish construction sector in conducting LCAs of new buildings and gaining knowledge in environmental product declarations (EPD) available for the Danish sector to apply. Eventually, this will enable more specific and transparent LCA results of Danish buildings. We investigate the availability and applicability of EPDs from a Danish perspective in the first part of the study, and in the second part, we investigate the influence on LCA results when applying industry- or product-specific data instead of generic data (Ökobau 2020 II). Three exterior wall types A, B and C are outlined based on the same U-value, and generic data are replaced with EPD data. The results show the various combinations possible with applying the EPD data. Secondly, the LCA results are highly dependent on the chosen materials and their corresponding EPD data.